2022
DOI: 10.3390/ijms23052656
|View full text |Cite
|
Sign up to set email alerts
|

CabZIP23 Integrates in CabZIP63–CaWRKY40 Cascade and Turns CabZIP63 on Mounting Pepper Immunity against Ralstonia solanacearum via Physical Interaction

Abstract: CabZIP63 and CaWRKY40 were previously found to be shared in the pepper defense response to high temperature stress (HTS) and to Ralstonia solanacearum inoculation (RSI), forming a transcriptional cascade. However, how they activate the two distinct defense responses is not fully understood. Herein, using a revised genetic approach, we functionally characterized CabZIP23 in the CabZIP63–CaWRKY40 cascade and its context specific pepper immunity activation against RSI by interaction with CabZIP63. CabZIP23 was or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 84 publications
(124 reference statements)
0
9
0
Order By: Relevance
“…By previous studies, CaWRKY40 is promoted to activate PR genes such as CaPR4 , CaPR1 , CaDEF1 , and CaHSP24 by CaWRKY27b and CaWRKY28 [ 23 , 58 ], and CaWRKY40 is repressed by CaSTH2 to activate the above-mentioned target genes not by repressing the direct targeting of these genes by CaWRKY40; we speculate that CaSTH2 might repress CaWRKY40 by blocking its interaction with CaWRKY27b or CaWRKY28. We used the BiFC assay to verify this assumption, and the results showed that the co-transient overexpression of CaSTH2 significantly reduced the CaWRKY40-CaWRKY27b/CaWRKY28 interaction ( Fig.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…By previous studies, CaWRKY40 is promoted to activate PR genes such as CaPR4 , CaPR1 , CaDEF1 , and CaHSP24 by CaWRKY27b and CaWRKY28 [ 23 , 58 ], and CaWRKY40 is repressed by CaSTH2 to activate the above-mentioned target genes not by repressing the direct targeting of these genes by CaWRKY40; we speculate that CaSTH2 might repress CaWRKY40 by blocking its interaction with CaWRKY27b or CaWRKY28. We used the BiFC assay to verify this assumption, and the results showed that the co-transient overexpression of CaSTH2 significantly reduced the CaWRKY40-CaWRKY27b/CaWRKY28 interaction ( Fig.…”
Section: Resultsmentioning
confidence: 73%
“…2C ), lower level of bacterial growth at 48 and 72 hpi ( Fig. 2D ), as well as upregulation of immunity-related CaPR1 , CaPR4 , and CaDEF1 [ 23 ] in contrast to plants of the wild type ( Fig. 2E ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations